Enhancing noncommunicable public health programs: A system dynamics approach to understanding reach, maintenance, and implementation costs - Chiu, Simon Keith; Hall, Alix; Freebairn, Louise (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2025)
Introduction Noncommunicable diseases (NCDs) cause an estimated 41 million deaths globally each year, with cardiovascular diseases, cancers, chronic respiratory diseases, and diabetes being the leading contributors. Modifiable risk factors elevate the risk of NCDs. Despite the availability of effective prevention programs, their consistent implementation remains limited, highlighting the need for strategies to improve delivery and reduce costs. The reach, efficacy, adoption, implementation, and maintenance (RE-AIM) framework and system modelling can help in understanding and improvement of the implementation and maintenance of public health initiatives. Methods This research used a system dynamics model to explore hypothetical pathways between reach, maintenance, and the cost-related components of implementation within the RE-AIM framework. Scenarios explored the influence of strategies for enhancing reach and maintenance and the resulting impact on participation and cost. Results Scenarios that considered alternative pathways to engagement (i.e. enhanced reach strategies) and re-engagement led to higher participation rates by utilising alternative pathways and reducing dependence on initial reach. However, this increased overall program costs due to the population cycling between engagement and disengagement. Conclusion This modelling study highlights the complex non-linear relationships that affect the implementation of public health prevention, emphasising the need for support strategies to maintain engagement. The study shows that while alternative pathways to reach can improve participation, disengagement remains a significant challenge, impacting overall costs. Sustainment strategies that are both effective and cost-efficient are crucial for maintaining engagement and enhancing the effectiveness of public health programs.